SILICA-ALUMINA ACTIVE MATRIX DEVELOPMENT AS CRACKING CATALYST COMPONENT - Marina Nisa, Lita
Indonesia currently consumes the most petroleum in the transportation sector in the form of fuel oil (BBM) which can be produced through the Fluid Catalytic Cracking (FCC) process. The FCC process requires a catalyst consisting of zeolite, active matrix, filler and binder. The active matrix is an important component that performs the initial cracking and provides a large pore diameter for the diffusion of the heavy fraction components from the feed into the zeolite pores. Matrix can be synthesized with the main raw material in the form of kaolin which is abundant in Indonesia and additional material as a source of silica to meet the expected ratio. The hydrothermal method succeeded in obtaining an active matrix with a surface area of 545 m2/g (Qoniah et al., 2015). Thus, the hydrothermal hydrothermal method for preparing silica-alumina active matrix from kaolin is good for development. This study aims to determine the best Si/Al molar ratio using the hydrothermal method and determine the effect of aging time on matrix characteristics. The resulting matrices were characterized by X-ray Fluorescence (XRF), Nitrogen Physisorption by the Brunauer, Emmet, and Teller (BET) method, Ammonia Based Temperature-Programmed Adsorption/Desorption (NH3-TPD), X-ray Diffraction (XRD), Scanning Electron Microscope (SEM), and Micro-activity Test (MAT) with Vacuum Gas Oil (VGO) feed to obtain performance data, and gravimetry to obtain coke content data in spent matrix. The target matrix is expected to have a surface area of 350-600 m2/g and a pore diameter greater than 50 Å. Based on the research results, the synthesized matrix has a surface area of 44.26?88.43 m2/g and an average pore diameter in the range of 117.94?176.56 Å. The greater the Si/Al molar ratio, the lower the total acidity will be. The addition of aging time during matrix synthesis decreases the value of the physical characteristics and the total acidity of the matrix. The main product expected from the VGO cracking process is Light Cycle Oil (LCO). The highest LCO product was obtained at 18.78%-wt when using a matrix with a Si/Al molar ratio of 14 with a surface area of 88.43 m2/g, a pore diameter of 176.56 Å, and a total acidity of 0.13 mmol NH3/ g.